2006
DOI: 10.1152/ajpendo.00078.2006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet consumption results in fetal malprogramming predisposing to the onset of metabolic syndrome-like phenotype in adulthood

Abstract: . Maternal high-fat diet consumption results in fetal malprogramming predisposing to the onset of metabolic syndrome-like phenotype in adulthood. Am J Physiol Endocrinol Metab 291: E792-E799, 2006. First published May 23, 2006; doi:10.1152/ajpendo.00078.2006.-Chronic consumption of a high-fat (HF) diet by female rats in their postweaning period resulted in significant increases in body weight and plasma levels of insulin, glucose, and triglycerides during pregnancy compared with female rats consuming a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
191
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(218 citation statements)
references
References 41 publications
18
191
2
7
Order By: Relevance
“…Two rats receiving the same diet were housed per cage from the time of weaning until initiation of breeding. (Srinivasan et al 2006). The energy densities of the diets were 5 .…”
Section: Animal Experimentationmentioning
confidence: 99%
“…Two rats receiving the same diet were housed per cage from the time of weaning until initiation of breeding. (Srinivasan et al 2006). The energy densities of the diets were 5 .…”
Section: Animal Experimentationmentioning
confidence: 99%
“…Energy-dense diets have been reported to contain higher amounts of fat, refined grains and added sugars, while lower amounts of fruits and vegetables, whole-grains and dietary fiber (Kant and Graubard, 2005;Ledikwe et al, 2006b); such dietary intakes have been related to the high prevalence of the metabolic syndrome and its components in earlier studies (Srinivasan et al, 2006;Radhika et al, 2009;Malik et al, 2010). Furthermore, we are aware of just one report that evaluated dietary energy density in relation to the metabolic syndrome; where Mendoza et al (2007), using cross-sectional data from 1-day 24-h dietary recall in NHANES 1999-2002, found an independent positive association between dietary energy density and the metabolic syndrome among US adults.…”
Section: Introductionmentioning
confidence: 97%
“…It is demonstrated that metabolic diseases have their origin in early life nutritional experience such as maternal high-fat (HF) diet consumption during gestation and lactation (Srinivasan et al, 2006). The changes in energy balance and cells' response to insulin are the important metabolic changes in the offspring of HF-fed dams (Sullivan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%